2018
DOI: 10.3389/fchem.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity, Conductivity, and Electrochemical Property of Dicyanamide Ionic Liquids

Abstract: The instructive structure-property relationships of ionic liquids (ILs) can be put to task-specific design of new functionalized ILs. The dicyanamide (DCA) ILs are typical CHN type ILs which are halogen free, chemical stable, low-viscous, and fuel-rich. The transport properties of DCA ionic liquids are significant for their applications as solvents, electrolytes, and hypergolic propellants. This work systematically investigates several important transport properties of four DCA ILs ([C4mim][N(CN)2], [C4m2im][N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(72 citation statements)
references
References 37 publications
5
61
0
Order By: Relevance
“…These values indicated that the Arrhenius law fitted very well with the experimental data. As seen in Figure 4, all electrical conductivity of PILs increased with the increase of temperature, this trend fitted with other reports (Sayah et al, 2018; Yuan et al, 2018). In addition, among the synthesized PILs, [DMEA][OTf] had the highest conductivity at all investigated temperatures and [TEA][Bsa] had the lowest one at the same temperature range.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These values indicated that the Arrhenius law fitted very well with the experimental data. As seen in Figure 4, all electrical conductivity of PILs increased with the increase of temperature, this trend fitted with other reports (Sayah et al, 2018; Yuan et al, 2018). In addition, among the synthesized PILs, [DMEA][OTf] had the highest conductivity at all investigated temperatures and [TEA][Bsa] had the lowest one at the same temperature range.…”
Section: Resultssupporting
confidence: 90%
“…However, the viscosity of [TEA][OTf] and [DEA][OTf] was similar at the whole temperature range. As liquid viscosity was caused by the cohesion of molecules, the viscosity change law of investigated PILs could be explained by the interactions of molecules (Yuan et al, 2018). Benzene ring was a large group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs), consisting entirely of ions, are extensively studied in areas of electrochemistry and electrochemical devices due to their properties of a wide electrochemical window, high electric conductivity and electrochemical stability [27][28][29][30] . Recently, IL-polymer (ILP) composites have shown great performance in the field of electrochemistry, such as transparent solid electrodes, self-healing ionic conductors, conductive biofibres, etc.…”
mentioning
confidence: 99%
“…Dicyanamide ILs are generally obtained by the reaction of the chloride or bromide salt with AgN(CN) 2 . To avoid any silver contamination, TAAILs 29 – 40 were synthesized following a modified protocol of Boudesocque and co‐workers .…”
Section: Resultsmentioning
confidence: 99%